Diagnostic accuracy of a self-report measure of patellar tendinopathy in youth basketball - Owoeye, O. B. A.; Preston Wiley, J.; Walker, R. E. A.; Palacios-Derflingher, L.; Emery, C. A. (Journal of Orthopaedic & Sports Physical Therapy, 2018)
Study Design: Prospective diagnostic accuracy validation study. Background: Engaging clinicians for diagnosis of patellar tendinopathy in large surveillance studies is often impracticable. A self-report measure, the Oslo Sports Research Trauma Centre patellar tendinopathy (OSTRC-P) Questionnaire, an adaptation of the OSTRC Questionnaire may provide a viable alternative. Objectives: To evaluate the diagnostic accuracy of the OSTRC-P Questionnaire in detecting patellar tendinopathy in youth basketball players when compared to clinical evaluation. Methods: Following the Standards for Reporting of Diagnostic Accuracy Studies guidelines, 208 youth basketball players (aged 13-18 years) were recruited. Participants completed the OSTRC-P Questionnaire (index test) prior to a clinical evaluation (reference standard) by a physiotherapist blinded to OSTRC-P Questionnaire results. Sensitivity, specificity, predictive values (PVs), likelihood ratios (LRs) and posttest probabilities were calculated. Linear regression was used to examine the association between OSTRC-P Questionnaire severity score and patellar tendinopathy severity rating during single leg decline squat (SLDS). Results: The final analysis included 169 players. The OSTRC-P Questionnaire had a sensitivity of 79% (95%CI: 65%, 90%), specificity of 98% (95%CI: 94%, 100%), positive PV of 95%, negative PV of 92%, positive LR of 48 and negative LR of 0.21. The posttest probabilities were 95% and 8% given positive and negative results, respectively. A positive association was found between OSTRC-P Questionnaire and SLDS rating [(ß = .08 (95%CI: .03, .12) (p = .001)]. Conclusions: The OSTRC-P Questionnaire is an acceptable alternative to clinical evaluation for self-reporting patellar tendinopathy and grading its severity in settings involving youth basketball players.